A Comprehensive Prognostic and Immunological Analysis of a Six-Gene Signature Associated With Glycolysis and Immune Response in Uveal Melanoma - Liu, Jun; Lu, Jianjun; Li, Wenli (Frontiers in Immunology, 2021)
Uveal melanoma (UM) is a subtype of melanoma with a poor prognosis. This study aimed to construct a new prognostic gene signature that can be used for survival prediction and risk stratification of UM patients. In this work, transcriptome data from the Molecular Signatures Database were used to identify the cancer hallmarks most relevant to the prognosis of UM patients. Weighted gene co-expression network, univariate, least absolute contraction and selection operator (LASSO) and multivariate COX regression analysis were used to construct prognostic gene characteristics. Kaplan-Meier and ROC curves are used to evaluate the survival prediction ability of the gene signature. The results showed that glycolysis and immune response were the main risk factors for OS in UM patients. Using univariate Cox analysis, 238 candidates related to the prognosis of UM patients were identified (P<0.05). Using LASSO Cox analysis and multivariate Cox regression analysis, a six-gene signature including ARPC1B, BTBD6, GUSB, KRTCAP2, RHBDD3 and SLC39A4 was constructed. Kaplan-Meier analysis of the UM cohort in training set showed that patients with higher risk scores had worse overall survival (HR = 2.61, p <0.001). Time-dependent receiver operating characteristic (t-ROC) curve showed that the risk score had a good predictive efficiency for UM patients in the training set (AUC>0.9). Besides, tROC analysis showed that the predictive ability of risk scores was significantly higher than other clinicopathological characteristics. Univariate and multivariate Cox regression analysis showed that risk score was an independent risk factor for OS in UM patients. The prognostic value of the risk score was further verified in two external UM cohorts (GSE22138 and GSE84976). Two-factor survival analysis showed that UM patients with high hypoxia or immune response scores & high risk-scores had the worst prognosis. Moreover, a nomogram based on the six-gene signature was established for clinical practice. In addition, the risk score was related to the immune infiltration profiles. Taken together, this study identified a new prognostic six-gene signature related to glycolysis and immune response. This six-gene signature can not only be used for survival prediction and risk stratification, but also may be a potential therapeutic target for UM patients.